Transient manifestation of left ventricular diastolic dysfunction following ablation in patients with paroxysmal atrial fibrillation. Issue 7 (18th July 2018) - Minamisaka, Tomoko; Watanabe, Tetsuya; Shinoda, Yukinori; Ikeoka, Kuniyasu; Fukuoka, Hidetada; Inui, Hirooki; Ueno, Keisuke; Inoue, Soki; Mine, Kentaro; Hoshida, Shiro
Abstract : Background: In patients with atrial fibrillation, ablation decreases left atrial (LA) compliance, which may lead to left ventricular (LV) diastolic dysfunction. We aimed to examine serial changes in LV diastolic function after 2 ablation procedures and their related factors in patients with paroxysmal atrial fibrillation (PAF). Hypothesis: LV diastolic function is different after 2 ablation procedures. Methods: We enrolled 132 patients with PAF (76 males, mean age 67 years; cryoballoon [CB] ablation/radiofrequency [RF] ablation 60/72) who underwent a single ablation procedure. The transthoracic echocardiographic parameters were obtained before, 3 days after, and 6 months after ablation. Results: The afterload‐related index of LV diastolic function, Ed/Ea = E/e' / (0.9 × systolic blood pressure), increased significantly at 3 days after ablation, especially after CB ablation ( P <0.05), although no differences were observed in age, sex, LA size, LV size, and E/e' before ablation between CB ablation and RF ablation. Creatine kinase release after ablation was significantly higher in CB ablation than in RF ablation ( P <0.001). The increment of Ed/Ea after CB ablation was positively correlated with LV ejection fraction (LVEF) before ablation ( r =0.416; P <0.05). The elderly (age ≥ 75 years), females, and patients with hypertension were more likely to show impaired LV diastolic function transiently after 3 days of ablation, but the diastolic index was restored to baseline level after 6 months. Conclusions: The increased Ed/Ea after CB ablation represented transient manifestation of underlying LV diastolic dysfunction in PAF patients with preserved LVEF with older age, female sex, and a history of hypertension.